2023
DOI: 10.3390/nu15071739
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Fluid Intake, Hydration Status, and Health Effects among Pregnant Women in Their Second Trimester in China: A Cross-Sectional Study

Abstract: The fluid intake and hydration status during pregnancy may influence the health outcomes of both the mother and the fetus. However, there are few studies related to this. The aim of the present study was to investigate fluid intake behaviors among pregnant women in their second trimester, to evaluate their hydration status and pregnancy complications, and to further explore the association of fluid intake and the amniotic fluid index (AFI). Participants’ total fluid intake (TFI) levels were determined using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 63 publications
1
8
1
Order By: Relevance
“…Our findings also highlight the need for education and increased knowledge prior to conception and early in the pregnancy to continue healthy hydration behaviors throughout the entire pregnancy and into postpartum as many women were not meeting the hydration recommendations. This gap may increase the risks for adverse pregnancy and postpartum outcomes (i.e., excessive gestational weight gain, hypertensive disorders, preterm births, and gestational diabetes [ 32 ]), which increases the risk for maternal mortality. Thus, there is a need for strategies to promote knowledge and adequate intake recommendations and strategies during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings also highlight the need for education and increased knowledge prior to conception and early in the pregnancy to continue healthy hydration behaviors throughout the entire pregnancy and into postpartum as many women were not meeting the hydration recommendations. This gap may increase the risks for adverse pregnancy and postpartum outcomes (i.e., excessive gestational weight gain, hypertensive disorders, preterm births, and gestational diabetes [ 32 ]), which increases the risk for maternal mortality. Thus, there is a need for strategies to promote knowledge and adequate intake recommendations and strategies during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…There were several strengths of this study, one of which was that it was one of the first to understand pregnant women’s thoughts, beliefs, preferences, and needs regarding hydration, hydration behaviors, and the use of digital tools overall but also based on trimester. Previous research has focused on associations of hydration levels on pregnancy outcomes [ 10 , 35 ], measuring hydration levels during pregnancy [ 11 , 32 ] and intravenous hydration [ 36 ], while this study focused on understanding how researchers can promote hydration behaviors during pregnancy. These findings highlight the major knowledge and research gaps when it comes to hydration behaviors during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on water intake among pregnant women in Mexico [ 22 ], Indonesia [ 23 ], and Hainan [ 21 ] only evaluated TFI and did not consider water from food. In fact, the water in food plays an important role in replenishing the body’s water.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Erica Perrier et al in adults [ 28 ] also confirmed that there was a positive correlation between fluid intake and 24 h urine volume ( r = from 0.74 to 0.79), while there was a negative correlation between fluid intake and 24 h urine osmolality, USG, as well as the concentrations of sodium, potassium, phosphorus, creatinine, urea, and uric acid, respectively ( r = from −0.49 to −0.73). In the latest study of pregnant women in Haikou [ 21 ], it was also found that fluid intake was negatively correlated with morning urine osmolality and USG in pregnant women in Haikou ( r = from −0.397 to −0.111). However, the correlation coefficient was lower than the results in our study, which may be attributed to the morning urine collected in this study, rather than the 24 h urine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation